Islam, Fatwa dan Negara: Meretas Pluralisme Hukum Perceraian di Aceh - Muhazir Muhazir (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2021)
The pluralism of divorce in Aceh has had an impact on the current practice of divorce. Fatwa, Jurisprudence, and the State also color the pluralism of divorce law, each of which has a normative and sociological power base. The Aceh MPU's fatwa tends to legitimize divorce regulated in fiqh books while the State has a different view of divorce law. This paper is a doctrinal study with a legal pluralism approach. This article argues that in substance there is a significant difference between the divorce provisions in the fatwa, fiqh, and state law. Fatwa and fiqh share the same view that divorce without witnesses and taking place outside the court is still valid, as well as triple talaq, whether pronounced cumulatively or separately, is still subject to triple talaq, this provision is different from divorce law which is regulated by the state and practiced in religious courts.